2010
DOI: 10.1161/circulationaha.110.956730
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor 7 Knockout Attenuates Atherosclerotic Plaque Development

Abstract: Background-Atherosclerosis is a systemic inflammatory disease characterized by the formation of atherosclerotic plaques. Both innate immunity and adaptive immunity contribute to atherogenesis, but the mode of interaction is poorly understood. Chemokine receptor 7 (CCR7) is critically involved in the transition from innate to adaptive immune activation by coordinating the migration to and positioning of antigen-presenting dendritic cells and T cells in secondary lymphoid organs. More recently, it was shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 33 publications
5
57
0
Order By: Relevance
“…Moreover, during hypercholesterolemia, DCs as well as CCL17 + DCs can be sequestered in the periphery (60) and may thus present antigens such as oxLDLor LDL-derived peptides in lymphoid tissue. Notably, a recent study employing Ccr7 -/-mice provided evidence supporting the hypothesis that local priming processes in the inflamed vessel wall or lymphoid tissue alone are insufficient to generate or maintain an adaptive immune response promoting atherogenesis; and that CCR7-dependent trafficking of T cells to draining LNs and their (re)entry to sites of inflammation are essential (61).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, during hypercholesterolemia, DCs as well as CCL17 + DCs can be sequestered in the periphery (60) and may thus present antigens such as oxLDLor LDL-derived peptides in lymphoid tissue. Notably, a recent study employing Ccr7 -/-mice provided evidence supporting the hypothesis that local priming processes in the inflamed vessel wall or lymphoid tissue alone are insufficient to generate or maintain an adaptive immune response promoting atherogenesis; and that CCR7-dependent trafficking of T cells to draining LNs and their (re)entry to sites of inflammation are essential (61).…”
Section: Discussionmentioning
confidence: 92%
“…Other studies restricted monocyte entry using CX3CR1-deficient mice (21) or inhibited monocyte differentiation into DCs using GM-CSF-deficient mice (11) or restricted DC egress from lesions using CCR7-deficient mice (36). In all these mouse models, atherosclerosis was deceased, not increased as in the Cre + model, suggesting a proatherogenic role for DCs.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CCR7 in atherogenesis is, however, more controversial due to the demonstration that CCR7 is important for macrophage emigration out of established atherosclerotic plaques in an aortic transplantation model of atherosclerosis (Trogan et al, 2006;Feig et al, 2010Feig et al, , 2011a. Ablation of the CCR7 gene in Ldlr 2/2 mice followed by 12 weeks of a high-fat diet was associated with reduced plaque size and reduced numbers of both CD68 1 cells (macrophages) and CD11c 1 cells [macrophages and DCs (Luchtefeld et al, 2010)]. An intriguing recent publication from the Fisher and Garabedian laboratories demonstrated that Apoe 2/2 mice a high-fat diet and treated with either atorvastatin or rosuvastatin demonstrated no change in atherosclerotic plaque area but did show significant reductions in CD68 1 macrophage staining area (Feig et al, 2011b).…”
Section: Luchtefeld Et Al 2010mentioning
confidence: 99%